2020
DOI: 10.1007/s10826-020-01737-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “SIBS”, An Intervention for Siblings and Parents of Children with Chronic Disorders

Abstract: Siblings of children with chronic disorders are at increased risk of experiencing family communication problems and poorer mental health. We assessed initial feasibility, acceptability, and outcomes of SIBS; a manual-based group intervention for siblings and parents of children with chronic disorders, aiming to improve parent-sibling communication and sibling mental health. Ninety-nine siblings aged 8-16 years (M = 11.5 years, SD = 2.0; 54.5% girls) and parents (63.6% mothers) of children with chronic disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 55 publications
1
61
2
1
Order By: Relevance
“…This is in contrast to norm data from Britain and Australia, on which self-report is typically higher than parent report (Mellor, 2005;Meltzer et al 2003). In the Norwegian SIBS trial, siblings also self-reported more mental health problems than parents (Haukeland et al 2020). Although we do not know the reasons for the difference in sibling self-reported mental health and parent-reported mental health for siblings, discrepancy between child-and parent-report is common, and the norm rather than the exception in child mental health (De Los Reyes 2011).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…This is in contrast to norm data from Britain and Australia, on which self-report is typically higher than parent report (Mellor, 2005;Meltzer et al 2003). In the Norwegian SIBS trial, siblings also self-reported more mental health problems than parents (Haukeland et al 2020). Although we do not know the reasons for the difference in sibling self-reported mental health and parent-reported mental health for siblings, discrepancy between child-and parent-report is common, and the norm rather than the exception in child mental health (De Los Reyes 2011).…”
Section: Discussioncontrasting
confidence: 79%
“…The 20-item PSSC-P was rated by caregivers. The PSSC-C/P has demonstrated good psychometric properties with Chronbach's α from .75 to .82 for PCCS (Haukeland et al 2020;Loeber et al 1998).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A preliminary version of the SIBS intervention was piloted with 58 families in 2013 and adapted based on participant feedback (25). The adapted SIBS intervention was then delivered to 107 families in our open trial in collaboration with the national user unions for autism, Down syndrome, cerebral palsy, and congenital heart disease [11]. We made further adaptations (e.g., longer breaks between sessions; removing questionnaires) based on feedback from these unions and participants for the current SIBS-RCT.…”
Section: User Involvementmentioning
confidence: 99%